Immigrant Irishwomen and maternity services in New York and Boston, 1860–1911. Issue 1 (January 2022) - Breathnach, Ciara
Abstract: Medical acculturation forms a crucial part of the process of migration, and equally, the influx of migrants can shape how medical structures develop in receiving societies – nowhere is that more evident than in the American metropolis. In the late nineteenth century, few ethnic groups caused such sustained bio-hazard concerns as the Irish in America. Poverty and the sheer numbers migrating in the post-Famine (1852-) era, caused the immigrant Irish body to be pathologised, or described in medical terms, to a much greater degree and for longer than their Anglo-Saxon or German counterparts. With a particular focus on Irishwomen's use of maternity services in New York and Boston, this article aims to elucidate the potential of medical records to flesh out the understandings of how immigrants navigated healthcare. By adopting a case study approach to hospital records in tandem with other data sources, it shows what is being lost through restrictive data protection legislation. It discusses how Irishness was politicised in the contexts of immigration, the social history of medicine and medicalisation.